2017
DOI: 10.31436/imjm.v16i2.322
|View full text |Cite
|
Sign up to set email alerts
|

Morphology of Maxillary First Molars Analyzed by Cone-Beam Computed Tomography among Malaysian: Variations in the Number of Roots and Canals and the Incidence of Fusion

Abstract: Introduction: A few studies investigated the numerous potential endodontic uses of CBCT, including the examination of root canal morphology and presumed that CBCT was effective for the initial identification of such morphology; moreover CBCT is a reliable method for the detection of the MB2 canal when compared with the gold standard of physical sectioning of the specimen. The aim of this study was to identify the root and canal morphology of the maxillary first molars among Malaysians analysed by cone-beam com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 16 publications
(29 reference statements)
1
15
0
Order By: Relevance
“…[2,6] Using similar imaging methods, Al-Kadhim et al reported that 98% of maxillary first molars have three separate roots, which is almost identical to our finding (97.7%). [21] Our result is also consistent with a study from our neighboring country, Thailand, which found that 99.8% of first molars and 87.1% of second molars have three roots. [6] However, we found a slight anatomical variation of maxillary first and second molars in Malay ethnic.…”
Section: Rootsupporting
confidence: 93%
See 3 more Smart Citations
“…[2,6] Using similar imaging methods, Al-Kadhim et al reported that 98% of maxillary first molars have three separate roots, which is almost identical to our finding (97.7%). [21] Our result is also consistent with a study from our neighboring country, Thailand, which found that 99.8% of first molars and 87.1% of second molars have three roots. [6] However, we found a slight anatomical variation of maxillary first and second molars in Malay ethnic.…”
Section: Rootsupporting
confidence: 93%
“…[14][15][16][17][18][19][20] Recently, more studies have been utilizing CBCT as a method to study root and canal morphology. [6,[21][22][23][24][25][26][27][28][29][30][31] CBCT imaging is more accurate, effective, and reliable as a diagnostic tool compared to other imaging modalities and conventional methods. [23,32] For clinical settings, the American Association of Endodontics and American Academy of Oral and Maxillofacial Radiology recently came up with a comprehensive guideline regarding the use of CBCT imaging in endodontics for the initial assessment of teeth with suspected additional canals and second molars than females.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Limited information is available on the root and canal morphology in the Malaysian population using CBCT (20,21). This CBCT study aimed to evaluate the root and root canal morphology of permanent anterior dentition in relation to ethnicity, gender and age of patients in a Malaysian population using two classification systems.…”
Section: Introductionmentioning
confidence: 99%